PENGARUH PEMBERIAN SANKSI PAJAK DAN KEAKTIFAN PENAGIHAN PAJAK DENGAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK - Nurhafifah; Elia Rossa; Wastam Wahyu Hidayat (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2022)
This research was conducted with the aim to examine the effect of tax sanctions and tax collection activities with forced letters on tax revenues. The subject of this research is WP OP Bekasi Regency who resides or is in the Cibitung Pratama Tax Service Office which is located at Ruko Pasar Modern Harapan Indah Boulevard No. 19 Harapan Indah Complex, Pusaka Rakyat, Taruma Jaya, Bekasi Regency, West Java 17214. This research is a survey research with data collection technique that is incidental sampling. The number of WP OP sampled in this study was 100 people. The approach used is a quantitative approach. The method used is a survey method by taking data directly to the field. The distribution of the questionnaires starts from April to May 2021. The analytical method used is the statistical analysis method, namely multiple linear regression analysis using test equipment or statistical applications, namely the Statistical Package for Social Science (SPSS). The results of this study indicate that the provision of tax sanctions and active tax collection with forced letters has a positive and significant effect on tax revenues, either partially or simultaneously.